Bioorthogonal Click and Release Reaction of Iminosydnones with Cycloalkynes. (9th November 2017) - Bernard, Sabrina; Audisio, Davide; Riomet, Margaux; Bregant, Sarah; Sallustrau, Antoine; Plougastel, Lucie; Decuypere, Elodie; Gabillet, Sandra; Kumar, Ramar Arun; Elyian, Jijy; Trinh, Minh Nguyet; Koniev, Oleksandr; et al.
Abstract: We report the discovery of a new bioorthogonal click‐and‐release reaction involving iminosydnones and strained alkynes. This transformation leads to two products resulting from the ligation and fragmentation of iminosydnones under physiological conditions. Optimized iminosydnones were successfully used to design innovative cleavable linkers for protein modification, thus opening up new areas in the fields of drug release and target‐fishing applications. This click‐and‐release technology offers the possibility of exchanging tags on proteins for functionalized cyclooctynes under mild and bioorthogonal conditions.